2021
DOI: 10.1021/acsaelm.0c01120
|View full text |Cite
|
Sign up to set email alerts
|

Organoiodine Functionality Bearing Resists for Electron-Beam and Helium Ion Beam Lithography: Complex and Sub-16 nm Patterning

Abstract: Given the current need for resist materials for patterning transistors with ultralow nodes, there has been a quest for developing resists with improved performance for nanoscale patterning with good contrast. The present work demonstrates polymeric resists (MAPDST-TIPMA) developed through the integration of a radiation-sensitive monomer (MAPDST) with an organoiodine functionality (TIPMA) for sub-16 nm patterning using electron-beam and helium ion beam lithography. The structural integrity was established by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…In the past decades, the miniaturization and improvement of electronic devices were mainly enabled by the rapid development of lithography technology and the improvement of resist performance . Electron beam lithography (EBL) and extreme ultraviolet lithography (EUVL), as the most advanced high-resolution lithography technologies, are widely used in research and high-volume production for feature sizes lower than 20 nm half-pitch (HP). Accordingly, the development of resist materials fulfilling the stringent requirements of high resolution ( R ), sensitivity ( S ), and low line edge roughness (LER) is still a great challenge for advanced lithography. ,, Although traditional chemically amplified resists (CARs) have been widely used in the semiconductor industry due to their high sensitivity, the stochastic distribution of photoacid generators (PAGs) and the diffusion of acids in the resist film result in poor LER and limit the resolution of CARs. ,, To overcome these limitations, researchers have proposed methods to accomplish the uniform distribution of PAGs and diffusion minimization of acids in a resist film. , It has been demonstrated that incorporating the PAGs into the polymer backbone and increasing the volume of anions of PAG can effectively improve the uniformity of PAG distribution and control the acid diffusion. However, as the feature size becomes smaller and smaller, it is difficult to achieve the required resolution due to the acid diffusion blur, which is intrinsic for CARs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decades, the miniaturization and improvement of electronic devices were mainly enabled by the rapid development of lithography technology and the improvement of resist performance . Electron beam lithography (EBL) and extreme ultraviolet lithography (EUVL), as the most advanced high-resolution lithography technologies, are widely used in research and high-volume production for feature sizes lower than 20 nm half-pitch (HP). Accordingly, the development of resist materials fulfilling the stringent requirements of high resolution ( R ), sensitivity ( S ), and low line edge roughness (LER) is still a great challenge for advanced lithography. ,, Although traditional chemically amplified resists (CARs) have been widely used in the semiconductor industry due to their high sensitivity, the stochastic distribution of photoacid generators (PAGs) and the diffusion of acids in the resist film result in poor LER and limit the resolution of CARs. ,, To overcome these limitations, researchers have proposed methods to accomplish the uniform distribution of PAGs and diffusion minimization of acids in a resist film. , It has been demonstrated that incorporating the PAGs into the polymer backbone and increasing the volume of anions of PAG can effectively improve the uniformity of PAG distribution and control the acid diffusion. However, as the feature size becomes smaller and smaller, it is difficult to achieve the required resolution due to the acid diffusion blur, which is intrinsic for CARs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, various types of n-CARs containing various radiation-sensitive groups, e.g., sulfone, , carbonate, , Sn–C bond, oxalate, and sulfonium groups, , have been reported. The resolution of resist materials containing sulfone, carbonate, , and oxalate was demonstrated to be around 20–30 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the phenolic hydroxyl groups of AD-10OH were protected with the t-Boc group in the presence of 4-dimethylaminopyridine, which provided monodisperse AD-10Boc in an 81% yield. Formation of the final product AD-10Boc was confirmed by 1 H NMR, 13 C NMR, FT-IR, and high-resolution ESI-TOF mass spectra, which are displayed in Fig. S5-S8 (ESI †).…”
Section: Synthesis Of Ad-10bocmentioning
confidence: 93%
“…However, it is still a challenge to develop resist materials fulfilling the requirements such as high sensitivity and low line-edge roughness (LER) simultaneously. [13][14][15] The commercially available non-chemically amplified resists (n-CARs), poly(methyl methacrylate) (PMMA) and hydrogen silsesquioxane (HSQ) achieved sub-10 nm patterns at the expense of high exposure dose. 2,3,[16][17][18][19][20] Gonsalves et al designed a nonchemically amplified polymeric hybrid resist based on the radiation-sensitive sulfonium functionality and organotin.…”
Section: Introductionmentioning
confidence: 99%